Nasal Septal Deviation After Surgically Assisted Rapid Maxillary Expansion - Seidita, Francesco; de Azambuja Carvalho, Pedro Henrique [UNESP]; Dos Sántos, José Cleveilton [UNESP]; Dell’Aversana Orabona, Giovanni; Califano, Luigi; Gabrielli, Mário Francisco Real [UNESP]; Filho, Valfrido Antonio Pereira [UNESP] (Springer Nature, 2021)
Background and Aim: Surgically assisted rapid maxillary expansion (SARME) is a surgical technique widely used to correct deficiency of the transverse maxillary dimension. Although some studies investigated the effect of SARME on nasal and facial alterations, there is no evidence that correlates nasal septal deviation (NSD) to SARME as a possible postoperative sequel. The aim of this study is to address and quantify possible variations in the position of the nasal bony septum after SARME and identify any NSD as a postoperative outcome of this surgical technique. Patients and Methods: This is a retrospective study, conducted at the Department of Oral and Maxillofacial Surgery of the University Hospital of Araraquara (Unesp, faculty of dentistry), SP, Brazil. Twenty-nine patients who underwent SARME were studied; every patient was evaluated by cone-beam computerized tomography (CBCT) before (T0) and six months after surgery (T1), and we collected the variation of nasal septal position by measuring the distance between the bony septum and the nasal lateral wall. Our measurements were carried out at the level of the head, midpoint and tail of the inferior turbinate. Results: A mean NSD ranging from 0.4 to 1.2 mm was measured, and it is more pronounced at the anterior part of the bony septum. Twenty-seven patients (93.1%) presented minor changes in bony septum position; in 2 cases (6.8%), a significant NSD was found (p < 0.05). Conclusion: A variation of bony nasal septum position can be expected in any direction after SARME, and it is more pronounced at anterior portion.